Reflections and translations are instances of transformation.
The rule of function g for the given reflection and translation is [tex]g(x) =-6x + 5[/tex]
Given
[tex]f(x) = 6x[/tex]
The rule of translating 5 units up is:
[tex](x,y) \to (x,y+5)[/tex]
So, we have:
[tex]f'(x) = f(x) +5[/tex]
[tex]f'(x) = 6x +5[/tex]
The rule of reflecting about the y-axis is:
[tex](x,y) \to (-x,y)[/tex]
So, we have:
[tex]g(x) =f(-x)[/tex]
[tex]g(x) =6(-x) + 5[/tex]
[tex]g(x) =-6x + 5[/tex]
Hence, the rule of function g is: [tex]g(x) =-6x + 5[/tex]
Read more about function transformations at:
https://brainly.com/question/13801312